TINDAK KEKERASAN DALAM RUMAH TANGGA : DITINJAU DARI UU PKDRT NO. 23 TAHUN 2004 DAN ALQURAN SURAT ANNISA: 34 - habib, Muhammad (AT-TAFAHUM: Journal of Islamic Law, 2017)
Islam forbids violence against anyone except to defend oneself from the enemy. With the PKDRT Law, this law is certainly in line with the essence of the Koran which prohibits anyone from committing acts of domestic violence. However, the presence of Annisa's letter: 34 seems to give the impression that Allah swt,. allow the husband to beat his wife if she commits nusuz/does domestic violence. Given the contradiction between the PKDRT Law and Annisa Letter: 34, this paper tries to unravel, find a middle way, and a solution to this contradiction, because Allah swt., it is impossible to order someone to do wrong to others, including his wife.